Evaluation of preliminary plant design for Chlorella vulgaris microalgae production focused on cosmetics purposes. (October 2020) - Caicedo, Y; Suarez, C; Gelves, G
Abstract: Although there are currently different large-scale microalgae production systems, its performance is subject to high production cost problems. That is why the main goal of this research is analyzing the feasibility of obtaining the Chlorella vulgaris microalgae from a proposed preliminary industrial plant design, considering its use in the cosmeceutical industry as skin care. Parameters used in the SuperPro Designer simulations were programmed based on experimental data reported from bibliography. For biomass and cell extract production, a Bold Basal enriched medium at 1% with soy flour was used. It is found that mass flow significantly affects production costs since a product value of 8.58 USD/ml was estimated operating the plant with 20 kg/h of mass flow. Interestingly 84 % unit reduction cost was improved by operating the proposed plant at 140 kg/h mass flow since 1.34 USD/ml of cosmetic product was determined. These findings show the potentiality of Chlorella vulgaris to be positioned in the world market. The latter, by considering its dependence on a successfully large scale plant. The above, in order to identify potential improvements focused on maximizing productivity and profits at the lowest operating cost.